FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK UMKM DI KELURAHAN KELAPA GADING TIMUR - Soros, George; Yuniarwati, Yuniarwati (Jurnal Paradigma Akuntansi, 2024)
This study aims to analyze how the role of tax socialization, tax morality, and perceptions of justice on the compliance of MSME taxpayers in Kelapa Gading Timur Village. The method chosen in this research is non-probability sampling and purposive sampling method. The valid data sample is 100 respondents. The results of data collection processed by Microsoft Excel 2013 and the SPSS program (Statistical Product and Service Solution) 25. The results of the research carried out show that partially taxation socialization, tax morality, and perceptions of justice have a positive and significant effect on taxpayer compliance. The implication of this research is the need to increase socialization for MSME taxpayers regarding the importance of taxation, where there are still many taxpayers who do not understand and understand their tax obligations.